Dystocia due to monocephalus tetra pus tetrabrachius fetus in a pleuriparous buffalo - CHEEDE, G S; BEDI, M K; MISHRA, Y; DADARWAL, D (The Indian Journal of Animal Reproduction, 2005)
Dystocia due to monocephalus tetrapus tetrabrachius fetus in a pleuriparous buffalo is put on record in the presentcommunication.
Keywords: Buffalo; dystocia; monocephalus tetrapus tetrabrachius